2013
DOI: 10.1097/pas.0b013e3182841554
|View full text |Cite
|
Sign up to set email alerts
|

Most Nonparotid “Acinic Cell Carcinomas” Represent Mammary Analog Secretory Carcinomas

Abstract: Acinic cell carcinoma (ACC) is a low grade salivary gland malignancy characterized by serous acinar differentiation. Most ACCs arise in the parotid gland, but ACCs have been reported to originate in non-parotid salivary glands where where serous acini are less abundant. Given the recent discovery of mammary analogue secretory carcinoma (MASC) – a salivary malignancy that histologically mimics ACC – a retrospective re-evaluation of non-parotid ACCs is warranted. The surgical pathology archives of The Johns Hopk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
187
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(195 citation statements)
references
References 17 publications
8
187
0
Order By: Relevance
“…A recent study has suggested that 'acinic cell carcinomas' that occur outside of the parotid are actually mammary analog secretory carcinomas. 15 A higher incidence of nodal metastasis and poorer disease-free survival seem to occur when compared with acinic cell carcinoma. 3,4 Figure 3 Adenocarcinoma, NOS.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has suggested that 'acinic cell carcinomas' that occur outside of the parotid are actually mammary analog secretory carcinomas. 15 A higher incidence of nodal metastasis and poorer disease-free survival seem to occur when compared with acinic cell carcinoma. 3,4 Figure 3 Adenocarcinoma, NOS.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of MASCs typically demonstrate coexpression of S100 protein and mammaglobin, although focal weak or absent expression of S100 protein has been reported in intraoral tumors [1,[22][23][24]. Using the above histologic features as a springboard for diagnosis as well as supporting coexpression of S100 protein and mammaglobin, we rendered a diagnosis of MASC in total of 19 consultation cases sourced from the University of Virginia and the Mount Sinai Health System-Beth Israel Medical Center.…”
Section: Discussionmentioning
confidence: 99%
“…In our experience the histologic and cytologic features of adenoid cystic carcinoma allow its easy distinction from MASC; although, in cases with high-grade transformation molecular studies would be prudent. Recently, MASC have been described in the oral cavity [22,24]. Given the predilection of polymorphous low-grade adenocarcinoma (PLGA) for this site, this tumor may enter the differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secretory carcinoma differs from acinic cell carcinoma epidemiologically in that the sex predilection is more equal, and secretory carcinoma arise in minor salivary sites more frequently than acinic cell carcinoma [3,5]. Histologically, secretory carcinoma share nearly identical growth patterns to acinic cell carcinoma (Fig.…”
Section: Secretory Carcinomamentioning
confidence: 99%